ANALYSIS OF HOMICIDAL DEATHS IN PESHAWAR, PAKISTAN - Marri, Murad Zafar; Bashir, M. Zahid; Munawar, Anjum Zia; Khalil, Zahid Hussain; Khalil, Inayat urRehman (Journal of Ayub Medical College Abbottabad, 2006)
Background: Homicide is one of the oldest crimes in human civilization. For every person who dies as a result of homicide, many more are injured. A study of the patterns of homicide in a society is one of the first steps in developing strategies to prevent it. This study was conducted at the department of Forensic Medicine Khyber Medical College, Peshawar, to know the patterns of homicide, taking it as the first step in the prevention of this crime. Methods: This study includes 520 cases of homicide out of the total of 662 medico-legal autopsies conducted at Khyber Medical College, Peshawar, during the year 2002. The cases have been labeled as homicide on the basis of autopsy and police inquest. Results: The homicide rate for Peshawar during the period under study was 22.9/100,000. Males constituted 86.15% of the victims. 32% of the victims were in their third decade of life. Firearms were the causative agent in 86% of the cases. Chest was the primarily targeted area of the body. The highest number of homicides occurred in the month of November. Conclusions: The homicide rate is alarmingly high in Peshawar as is the use of firearms. This is something that should be seriously looked at by the policy makers